Implementasi Pendidikan Warga Gereja Meneguhkan Sikap Etika Moral Menjawab Pengaruh Disrupsi Teknologi - Emilia Mude (Integritas: Jurnal Teologi, 2022)
This article is based on empirical observation concerning the impact of information and communication technology disruptions upon global, regional, national, and local communities around the globe. The methodology and methods implemented in this research is qualitative in nature and literature descriptive analysis methods to analyse core concepts and to display findings about how to implement Education of Church Members to strengthen ethics and moral life in facing the impacts of information and communication technology disruption. The process implemented in this research is started by determining core concepts, analysing, displaying the findings, and making some propositions in conclusion. The final aim is to equip church members in Biblical ethics and moral teachings to strengthen their spiritual life in facing the 21st Century technological challenges in present situations.